The Effectiveness of Social Assistance Programs in Reducing Poverty in Bandar Khalifah Village - Armin Rahmansyah Nasution; Lucky Pratama Satria (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Poverty is a socioeconomic problem faced by every country, including Indonesia. This study aims to demonstrate the effectiveness of social assistance (Bantuan Sosial/Bansos) in alleviating poverty in Bandar Khalifah Village, Deli Serdang Regency. This study was conducted using the Analytic Network Process (ANP) method, a development of the AHP, which can analyze the relationship between criteria. Primary data were collected through interviews and field observations. The results show that Bansos is most effective when it focuses on improving the community's economy, especially through increasing household consumption. Other supporting factors include access to health services, improving the quality of education, the right amount of assistance, and accurate distribution. The Direct Cash Assistance (Bantuan Tunai Langsung/BLT) program has proven more effective in improving welfare than the BPNT and National Program for the Poor (Program Keluarga Harapan/PKH). These findings underscore the importance of an economic empowerment approach as a key component in poverty alleviation programs, while emphasizing the need for intersectoral coordination to strengthen the positive impact of Bansos in rural areas. This research provides a practical contribution to the development of more targeted and sustainable social policies.